The Effectiveness of ANBK Implementation in Raising the Educational Quality of Elementary School - Mahatika, Anis; Trisoni, Ridwal (Institut Agama Islam Negeri Lhokseumawe, 2022)
Abstract: The purpose of this research is to provide an overview of how the computer-based national assessment (ANBK) was implemented at SD Negeri 20 Baringin. The study employs descriptive survey methods within a qualitative paradigm. Unstructured interviews, observations, and documentation studies are used as data-gathering strategies. The principal, vice curriculum officer, and program coordinator were the informant sources. employing snowball sampling to identify informants. Miles and Huberman models are employed in data analysis methods. Data reduction, data visualization, conclusion drawing, and data verification are all steps in the data analysis process. The improvement of the uniformity of the educational process in schools is the primary goal of the computer-based national assessment. Exercises in literacy, numeracy, and environmental surveying are used to increase learner effectiveness. ANBK is put into effect in three stages. The initial step of preparation entails participant registration, parent socialization, an implementation plan, socialization of accreditation and academic accomplishment, and an implementation timetable. The program's organization and supporting staff, which includes supervisors and technicians, is the second stage. Infrastructure and facility preparation using computers, rules for implementation, minutes, and attendance requirements. Third, the literacy and character survey's first day was followed by two days of the implementation stage. Day two of the environmental surveys and counting The assessment step is completed using the findings of the coloured reports that are included on the education unit's report card. The ANBK program is funded by the Regular School Operational Assistance Fund. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan penyelenggaraan Assesmen Nasional Berbasis Komputer (ANBK) di SD Negeri 20 Baringin. Penelitian menggunakan paradigma kualitatif teknik survey deskriptif. Teknik pengumpulan data menggunakan wawancara tidak terstruktur, observasi, dan studi dokumentasi. Sumber informan berasal dari Kepala Sekolah, Wakil Kurikulum dan koordinator program. Penentuan informan menggunakan snowball sampling. Teknik analisis data menggunakan model Miles dan Huberman. Tahapan analisis data melalui reduksi data, display data, dan pengambilan kesimpulan serta verifikasi data. Tujuan utama Asesesmen Nasional berbasis komputer adalah untuk meningkatkan standarisasi proses pembelajaran di sekolah. Efektivitas pembelajarn dicapai melalui latihan literasi dan numerasi serta kegiatan survei lingkungan. ANBK dilaksanakan melalui tiga tahap. Pertama, tahap persiapan meliputi pendaftaran peserta, sosialisasi wali murid, jadwal pelaksanaan, sosialisasi akreditasi dan prestasi sekolah, jadwal pelaksanaan. Tahap kedua, organisasi program dengan personel pendamping terdiri dari pengawas dan teknisi. Persiapan sarana dan prasarana melalui computer, aturan pelaksanaan, notulensi, dan persyaratan kehadiran. Ketiga, tahap implementasi dilaksanakan selama dua hari, hari pertama survei literasi dan karakter. Hari kedua survei lingkungan dan penomoran. Tahap evaluasi dilaksanakan melalui hasil laporan berwarna yang tertera pada rapor satuan pendidikan. Sumber pendanaan program ANBK berasal dari Dana Bantuan Operasional Sekolah Reguler.